ANALISA PENGARUH PENAMBAHAN THERMAL ENERGY STORAGE PADA PEMANAS AIR TENAGA SURYA TIPE PLAT DATAR - Maharuli Maharuli; I Made Kartika; Harto Tanujaya (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: Solar energy, the renewable energy is only available at certain hour. So it is essential to develop efficient, economical solar thermal energy storage. Thermal energy storage (TES) systems provide several alternatives for efficient energy use and conservation. Phase change materials (PCMs) for TES are materials supplying thermal regulation at particular phase change temperatures by absorbing and emitting the heat of the medium. TES in general and PCMs in particular, absorb energy during the heating process as phase change takes place and release energy to the environment in the phase change range during a reverse cooling process. PCMs possesses the ability of latent thermal energy change their state with a certain temperature. Paraffin is the PCM used in this research. Paraffin is being added to a solar water heater to store thermal energy at daylight and supply the stored energy to the heat pipe when the sundown. From this research, it is found that the solar water heater with paraffin need longer heating time than the conventional solar water heater but it could provide steadier heating performance and warm water even when the sun was down.